Emotional Intelligence and Eating Disorders: Comparison by Gender in Taekwondo Athletes - Astuti, Galuh Puji; Fitri, Mustika; Williyanto, Septian (Physical Education, Health and Recreation Study Program, Universitas Insan Budi Utomo, Indonesia, 2023)
Emotional intelligence is necessary to manage emotions and feelings to have a positive impact on mental health. This study examines emotional intelligence and eating disorders in taekwondo athletes. The purpose of this study was to determine the relationship between emotional intelligence and eating disorders with mental health disorders in taekwondo athletes and to provide gender-specific comparisons. A quantitative sample of 29 taekwondo athletes aged 13-17 was used as a research method. The Trait Emotional Intelligence Adolescent Short Form model was used to measure emotional intelligence and the EAT-26 model was used to measure eating disorders. The data analysis technique uses a correlation test. Based on data processing and analysis using SPSS, the results show a relationship between emotional intelligence and eating disorders in 13-17-year-old male taekwondo athletes, and there was no relationship between emotional intelligence and eating disorders in female taekwondo athletes. The conclusion of this research is that there is a negative and significant relationship between emotional intelligence and eating disorders in adolescent taekwondo athletes.